PENGARUH KOMPENSASI FINANSIAL DAN PEMBERDAYAAN PEGAWAI TERHADAP KEPUASAN KERJA PEGAWAI PADA BADAN PERWAKILAN BKKBN PROVINSI SUMATERA BARAT - Melani Desra; Bustari Muchtar; Menik Kurnia Siwi (Universitas Negeri Padang, 2018)
This study aims to determine and prove how much influence Financial Compensation and Employee Empowerment in the BKKBN Agency of West Sumatra Province. This type of research is causative. Population in this research is all employees of BKKBN Agency of West Sumatera Province. While the sampling is taken by using population research with the number of 90 respondents. The sampling technique was conducted based on Population Research. Types of data used in this study are primary and secondary data. Data analysis techniques using multiple regression analysis techniques using SPSS version 15.00. The results of this study indicate that: 1) Financial Compensation and Employee Empowerment have a significant effect on employee job satisfaction. 2) Financial compensation is influential and not significant to employee job satisfaction, 3) Employee Empowerment have a significant effect on employee job satisfaction.Keyword: Financial Compensation, Employee Empowerment, and Job Satisfaction